Clearing the Smoke to See the Screen: Ideological Manipulation in Audiovisual Translation - Díaz Cintas, Jorge (Meta, 2012)
In this article, a critical and methodological approach is offered concerning the subject of manipulation and translation in the realm of the audiovisual. Taking the potentialities unleashed by the cultural turn in Translation Studies as a starting point, the paper first provides an overview of the main hurdles and issues at stake when adopting a line of enquiry centred around the realisation that the way in which cultural values are translated depends not only on linguistic asymmetries between languages but also on fundamental decisions based on power, dominance, and ideology. As part of a debate that could prove fruitful in the world of audiovisual translation (AVT), the concept of manipulation is discussed in detail and a distinction between technical and ideological manipulation is put forward. After considering the special case of censorship and some of the new developments in the use of subtitling as a tool for local empowerment, it is suggested that the boundaries of research into AVT should be pushed beyond its traditionally parochial linguistic sphere by focussing more on unmasking the rationale behind ideologically motivated changes and by contextualising them within a wider socio-cultural environment.